Lectotypifications, epitypifications and neotypifications in Zygophyllaceae species from South America - Godoy-Bürki, Ana C. (Phytotaxa, 2018)
Zygophyllaceae in South America is mostly represented by members of the subfamily Larreoideae, which distinguishes the arid and semi-arid regions of Argentina and Chile. The subfamily Tribuloideae is also distributed in the Southern Cone but represented only by three species in Argentina. Currently there are no actualized taxonomic studies of the family that may help to understand its origin and diversification and to serve as a framework for phylogenetical analyses. In this context, the present study provides 9 lectotypifications, 2 epitypifications and 2 neotypifications of names of Zygophyllaceae species from Argentina, Chile, Brazil and Bolivia.